Upgrading Quality of Biobriquette Coconut Shell (Cocos nucifera) and Coal with Microwave Drying Treatment - Rizka Wulandari Putri; Rahmatullah Rahmatullah; Susi Susanti; Suci Anggrani; Asty Maharani; Alek Al Hadi; Alieftiyani Paramitha Gobel; Iriani Reka Septiana (Universitas Darussalam Gontor, 2026)
Subbituminous coal is found abundantly in Indonesia, especially in Sumatra, has significant potential for use as a raw material for briquettes and bio-briquettes. Subbituminous coal is a type of medium-rank coal with low calorific value about 4500-5000 cal/g. Therefore, the combination of coal with coconut shell biomass can increase the calorific value and briquettes quality. This study aims to improve the quality of biobriquettes through variations in carbonization temperature, the ratio of coconut shells to sub-bituminous coal, and the microwave drying. The briquette production conducted with carbonization process in 2 hours with variation temperature used were 300°C and 400°C, and raw material ratios consisted of 0:100, 25:75, 50:50, and 75:25 with the addition of tapioca adhesive of 15%. Low temperature carbonization (300-400°C) improves fuel quality by removing moisture and volatile matter, resulting in bio-briquettes with high calorific values. The optimal raw material ratio helps reduce combustion exhaust emissions. The charcoal crushed, mixed, casted and dried with microwave drying at 800 Watt. Microwave treatment contributed significantly to the reduction of moisture and ash content. The product briquettes were analyzed based on proximate parameters. The best conditions were achieved at a 75% coconut shell: 25% coal and a carbonization temperature of 300°C, characterized by the highest calorific value (5655 cal/g), the lowest ash content (0.65%), and the lowest inherent moisture (7.74%) that meets briquette quality standards of PERMEN ESDM No. 47/2006, while the lowest volatile matter (42.93%) and the highest carbon (48.77%) was also achieved in 75% coconut shell: 25% coal.